Students’ Perspectives about Science Technology Engineering Art and Math in Application to Physics Measurement Equipment Projects - Nadia Azizah; Hadma Yuliani; Jhelang Annovasho; Mardaya Mardaya (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to describe student perspectives about STEAM in application to Measurement Physics Measuring Instrument Projects. Research focuses on 23 students enrolled in the Physics Education Study Program at the Palangka Raya State Islamic Institute. The research used descriptive qualitative-quantitative and utilize a Likert scale to conduct a survey. Five projects implemented in this research are DC voltmeter project, galvanometer project, project to determine spring constants, vernier caliper project made from bamboo, sensory equipment project to detect water levels. The integration of STEAM with each project is a holistic methodology that commences with empathetic identification of a problem, followed by ideation through testing, and culminating in the acquisition of knowledge from prototypes and literature to inspire further innovation. According to the results, the five projects described for the science component ( ), technology component ( ), engineering component ( ), art component ( ), and mathematics component ( ). In conclusion, five projects strongly approved as constructive project with STEAM application.